Perfil dos Principais Autores da Revista Brasileira de Educação Médica entre 2006 e 2015: Perspectivas para um Novo Futuro? - Hamamoto Filho, Pedro Tadao; Caramori, Jacqueline Teixeira (Associação Brasileira de Educação Médica, 2017)
ABSTRACT The social changes that Brazil has faced in the last years were accompanied by changes in medical education in such a way that it became a research object. Actually the initiatives to improve the human sources to work in health sciences education have led to an increase in the scientific output in medical education. Knowing the researchers' profile is important to understand medical education as a scientific field. Among us, in Brazil, their profiles could be inferred through the analyses of the main authors of articles published in the Brazilian Journal of Medical Education (RBEM) in the last ten years, because it is the national leading specialized journal in medical education. Therefore, in order to understand this field of investigation we performed a bibliometric study to characterize the main authors' profile of the RBEM from 2006 to 2015. We added all authors of scientific communications published in the period and we analyzed those with at least five publications. Their professional information was extracted from the Lattes Platform. Data were assessed descriptively. We identified 2,191 different authors and included thirty nine. Among the included authors, 64.1% are physicians and the others are psychologists, pedagogues, nurses and sociologists. The majority of authors (71.8%) completed graduation between 1970 and 1989. Almost 90% have a PhD degree and 46.2% acquired it in the 2000s. Forty one percent of the authors accomplished some specialization training in the field of education, mainly between 1990 and 2000. The majority of the authors (76.9%) are in the Southeast region of Brazil, especially in the state of São Paulo (48.7%). The mean interval from the first scientific publication to the first scientific publication in medical education was 22 years among the authors graduated in the 1970s. On the other hand, this interval decreased to 8.5 years for those graduated in the 1990s. We compared our data to other bibliometric data and to a historical perspective of Brazilian medical education in such a way that we can conclude that there is a consolidation of medical education as a research field with increasing specific professionalization of the interested investigators.

RESUMO As mudanças sociais pelas quais o Brasil passou nos últimos anos foram acompanhadas de mudanças na formação médica, que passa a ser, ela própria, objeto de pesquisa. De fato, as iniciativas de incentivo à formação de profissionais para atuação no ensino em saúde têm aumentado a produção científica na educação médica. Para compreender este campo de pesquisa, é importante conhecer o perfil de seus pesquisadores. No Brasil, um indicativo deste perfil poderia ser inferido com base nas características dos principais autores de artigos publicados no periódico especializado da área, a Revista Brasileira de Educação Médica (RBEM), na última década. Assim, para compreender a educação médica enquanto campo de pesquisa, realizamos um estudo bibliométrico para caracterizar o perfil dos principais autores da RBEM no período de 2006 a 2015. Foram identificados todos os autores de comunicações científicas publicadas na RBEM, incluindo para análise aqueles com pelo menos cinco publicações na revista no período. Suas informações profissionais foram extraídas de seus currículos publicados na Plataforma Lattes. Os dados foram analisados de forma descritiva. Foram identificados 2.191 autores, tendo-se analisado 39. Entre os autores analisados, 64,1% são médicos, e outros são psicólogos, pedagogos, enfermeiros e cientistas sociais. A maioria (71,8%) concluiu a graduação entre 1970 e 1989. Quase 90% dos autores têm doutorado, sendo que 46,2% concluíram o doutorado na década de 2000; 41% dos autores realizaram algum curso de especialização em ensino, principalmente nas décadas de 1990 e 2000; 76,9% dos autores estão no Sudeste, com 48,7% em São Paulo. O intervalo médio entre a publicação do primeiro artigo científico e o primeiro artigo em educação médica foi de mais de 22 anos entre os formados na década de 1970, enquanto para os formados na década de 1990 esse intervalo foi de 8,5 anos. Comparando os dados obtidos com referenciais bibliométricos e com uma perspectiva histórico-fatual da educação médica no Brasil, apontamos a consolidação da educação médica como campo de pesquisa, com a profissionalização específica crescente de seus investigadores.
Profile of the Main Authors of the Brazilian Journal of Medical Education between 2006 and 2015: Perspectives for a New Future?
Keywords: Bibliometrics; Education, Medical; Scientific Publication Indicators; Bibliometria; Educação Médica; Indicadores de Produção Científica